PENGARUH GAYA KEPEMIMPINAN KEPALA MADRASAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU DI MTS NEGERI 4 JOMBANG - Lutfiya Masruroh, Asmi; Suwandi (LPPM STAI Muhammadiyah Probolinggo, 2024)
Like many other things, the principal's leadership style and culture affect teachers' performance. The primary purpose of this study is to determine if the leadership style of madrasah principals has an effect on teacher performance at MTs Negeri 4 Jombang. The secondary purpose is to determine if organisational culture has an effect on teacher performance at MTs Negeri 4 Jombang. Lastly, we hope to uncover any interactions between these two factors. Findings (1) Teachers' performance is less affected by the principal's leadership style than anticipated in madrasahs. According to the results of the hypothesis testing (significance value 0.000 < 0.005) and the T count (3.522 < 1.984), the alternative hypothesis (Ho) is rejected and the null hypothesis (Ha) is accepted. (2) This study's findings demonstrate that company culture affects instructors' performance on the job. The hypothesis test results, which indicate a significance value of 0.000 < 0.005 and a T count result of 6.588 < 1.984, lead us to accept Ha and reject Ho. (3) The leadership style and organisational culture of the madrasah head have a substantial impact on teacher performance at MTs Negeri 4 Jombang. Due to the computed T value (significance value 0.000 < 0.005) and the calculated F value (20.284 < 2.7758), the alternative hypothesis (Ho) is rejected and the null hypothesis (Ha) is accepted.